Factors Related to Levels of Burnout and Job Satisfaction in Family Physicians (Cross-sectional Research) - İzzet Çeleğen; Sinemis Çetin Dağlı (Genel Tıp Dergisi)

(untitled)
Aim: The study aims to evaluate the burnout and job satisfaction levels of family physicians in terms of some variables.Method: The study is of cross-sectional type. It was held between 03.06.2019-03.09.2019. The sample was not selected in the study, the whole universe was tried to be reached. 255 family physicians working in Van province were included in the study. The participation rate is 82%.Results: The mean scores of the participants of the study; Maslach sensuality: 29.87 ± 3.5, achievement: 23.62 ± 3.5, insensitivity: 13.37 ± 3.5, total: 22.29 ± 3.54, Minnesota total: 3.03 ± 0.68.There is a significant difference between gender, compliance with the personality structure of the work, choosing the profession at its own will, thinking about quitting the job, presence of chronic illness, physical and social conditions in the workplace, and burnout scores (p <0.05).Although there was no difference between the satisfaction of the family medicine system, the future anxiety of the system, and the burnout scores according to the satisfaction of the wage, there was a significant difference in terms of job satisfaction scores (p <0.05)Conclusion: The study results show that family physicians feel moderate to high levels of fatigue and emotional fatigue related to their profession. High scores in the depersonalization sub-dimension indicate that this situation is reflected negatively on the people they serve. It has been determined that thoughts about the family medicine system have an effect on job satisfaction rather than burnout.